2022
DOI: 10.3390/en16010114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Inrush Hazard in Coal Seam Roof Based on the AHP-CRITIC Composite Weighted Method

Abstract: The more complex the hydrogeological conditions of a mine, the more likely the coal seam is to experience water inrush during the mining process, and the greater the degree of the water inrush hazard. The scientific and reasonable prediction of water inrush in mines with complex hydrogeological conditions is of great significance to the safe and efficient operation of coal mines. Taking the roof water inrush problem of the No. 3 lower coal seam in the Jisan Coal Mine as the research object, the factors affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The analytic hierarchy process (AHP) is a method of multi-criteria decision analysis that breaks down complex decision problems into multiple objectives or criteria and further divides them into hierarchical indicators. Experts use their experience to determine the importance between parts, resulting in a decision matrix which defines the weights of each factor [29,30].…”
Section: Analytic Hierarchy Processmentioning
confidence: 99%
“…The analytic hierarchy process (AHP) is a method of multi-criteria decision analysis that breaks down complex decision problems into multiple objectives or criteria and further divides them into hierarchical indicators. Experts use their experience to determine the importance between parts, resulting in a decision matrix which defines the weights of each factor [29,30].…”
Section: Analytic Hierarchy Processmentioning
confidence: 99%
“…The limestone of the Changxing Formation is commonly exposed within the mining area and is replenished by atmospheric precipitation. Studies by Shi Xianzhi et al [5], Yao Guanghua et al [15], Wang Zaiyong et al [16], Long Tianwen et al [17], and Xiao Lele et al [18] have shown that under conditions of fracture development due to mining activities, the limestone of the Changxing Formation supplied the mining site through channels such as karst and fractures.…”
Section: Water-inrush Situation In Coal Mines In the Mining Areamentioning
confidence: 99%
“…Choosing appropriate methods to determine the weights of various indicators for water inrush in the separated layers is an important way to improve the accuracy of evaluation results The analytic hierarchy process (AHP) and entropy weighting are common methods for determining subjective and objective weights [23,24]. In order to make the calculation of each indicator more reasonable and accurate, and to compensate for the shortcomings of a single weighting method, an improved weighted fusion method is proposed.…”
Section: Risk Assessment Of Water Inrush In the Bed Separation Based ...mentioning
confidence: 99%
“…In relation to the safety evaluation of potential mine roof water damage, Wu [22] proposed the "three graphs and double prediction method" to analyze roof water accumulation and improve the accuracy of prediction results. In recent years, other scholars [23,24] have proposed different improvements to this method for various geological conditions, and have searched for suitable roof water inrush risk assessment methods. For example, Li [25] established an indicator system and evaluated the risk of water inrush based on GIS and a network analytic hierarchy process for the karst aquifer in the southwest mining region.…”
Section: Introductionmentioning
confidence: 99%